Traditional Knowledge of the Ecology of Beluga Whales (Delphinapterus leucas) in the Eastern Chukchi and Northern Bering Seas, Alaska - Huntington, Henry P.; Koyuk, Point Lay and Shaktoolik, The Communities of Buckland, Elim (ARCTIC, 1999)
Traditional ecological knowledge (TEK) has been used opportunistically in biological studies of beluga whales (Delphinapterus leucas) in Alaska, but no previous research has documented this knowledge systematically. This first such effort, which took place in Norton Bay, Buckland, and Point Lay, Alaska, provided descriptions of migratory and local movements, feeding, calving, ecological interactions, and human influences on distribution and behavior. The results are consistent with those of previous studies but add considerable detail, including descriptions of avoidance and habituation responses to anthropogenic noise, which appear to depend in part on association with hunting activities. Making greater use of TEK will benefit both research and management by providing better information and by expanding the collaborative process developed through co-management. On a utilisé le savoir écologique traditionnel (SET) quand l'occasion se présentait, dans le cadre des études biologiques portant sur le bélouga (Delphinapterus leucas) en Alaska, mais ce savoir n'a jamais fait l'objet d'une étude systématique. Cette première tentative en ce sens, qui a été réalisée à Norton Bay, Buckland et Point Lay, en Alaska, a fourni des descriptions de déplacements migratoires et locaux, de nutrition, de mise bas, d'interactions écologiques et d'influences humaines sur la distribution et le comportement. Les résultats concordent avec ceux d'études précédentes, mais apportent de nombreux détails, y compris la description des réactions d'évitement et d'accoutumance au bruit anthropique, qui semble dépendre en partie de l'association avec les activités cynégétiques. Une plus grande utilisation du SET profitera à la fois à la recherche et à la gestion en fournissant de meilleures informations et en développant plus à fond le processus de collaboration créé par la cogestion.